2006
DOI: 10.1086/507416
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dust Shell Dynamics and Asymmetry for Six Mira‐Type Stars

Abstract: Interferometric observations of six Mira-type stars: R Aqr, CIT 3, Cyg, WAql, R Leo, and U Ori are reported. All measurements were made by UC Berkeley's Infrared Spatial Interferometer (ISI ), which is comprised of three 1.65 m telescopes using a heterodyne detection system currently operating at 11.15 m. All data were taken in a nonredundant east-west linear configuration of telescopes, at a variety of spatial frequencies, with baselines of up to 12 m. By fitting a smooth curve to the closure phase data, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 37 publications
2
49
0
Order By: Relevance
“…This D-type (dusty) symbiotic system consists of a 1.0-2.0 M Mira variable and a 0.6-1.0 M white dwarf (WD) (Hollis et al 1997;Boboltz et al 1997;Tatebe et al 2006;Gromadzki & Mikołajewska 2009) that accretes matter through a disk (e.g. Hollis et al 2000).…”
Section: R Aquariimentioning
confidence: 99%
“…This D-type (dusty) symbiotic system consists of a 1.0-2.0 M Mira variable and a 0.6-1.0 M white dwarf (WD) (Hollis et al 1997;Boboltz et al 1997;Tatebe et al 2006;Gromadzki & Mikołajewska 2009) that accretes matter through a disk (e.g. Hollis et al 2000).…”
Section: R Aquariimentioning
confidence: 99%
“…The object W Aql is a Mira variable with a period of 490 days and an amplitude of approximately 7 mag, ranging from 7.3 to 14.3 mag in the V band. Due to its variable nature, many different distance calculations have been made for W Aql (Danchi et al 1994;Groenewegen 1998;Tatebe et al 2006;Ramstedt et al 2009). At a distance of 400 pc (Whitelock et al 2008), this separation corresponds to 190 AU.…”
Section: Introductionmentioning
confidence: 99%
“…This would certainly cause extinction depending on the alignment of the system. Tatebe et al (2006) used the UC Berkeley Infrared Spatial Interferometer to resolve the distribution of emitting dust at 11.15 µm and found an asymmetry in the dust distribution around the primary on small scales (hundreds of mas), while Ramstedt et al (2011) find asymmetry on large scales (10 arcsec). Herschel/PACS photometry presented in Mayer et al (2013) shows a large (∼100 arcsec) dust envelope on the same general shape as Ramstedt et al (2011) found in the optical but with an bright patch of dust to the east of the star in both the 70 µm and 160 µm images.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of such small structures near evolved stars can only be performed with the use of high-angular resolution techniques like the infrared Very Large Telescope Interferometer (VLTI), i.e. planetary nebulae (Chesneau et al , 2007Lagadec et al 2006); VLTP star (Chesneau et al 2009); Mira stars (Tatebe et al 2006(Tatebe et al , 2007(Tatebe et al , 2008; carbon stars (Ohnaka & Boboltz 2008;Sacuto et al 2011;Deroo et al 2007b); OH/IR stars (Deroo et al 2007a,b;Chesneau et al 2005b); post-AGB stars (Deroo et al 2006;Matsuura et al 2006); proto-planetary nebulae (Murakawa et al 2008;Ohnaka et al 2006). Two of the best-studied examples of elongated and axisymmetric bipolar planetary nebulae are M2-9 and Menzel 3.…”
Section: Introductionmentioning
confidence: 99%